Efektifitas Belajar Lempar Cakram Menggunakan Media Modifikasi Piring Plastik untuk Meningkatkan Hasil Belajar Siswa Kelas VI SD Negeri 3 Suradadi - Akbar, Muhammad Syaiful (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
This study aims to increase the effectiveness of student learning through modification of plastic plates on disc games. This type of research uses Classroom Action Research (CAR) taking subjects of class VI SD Negeri 3 Suradadi totaling 35 people. The results showed a significant increase from each cycle. First, student activity in the learning process was categorized as active in the first cycle of 70%. Then in the second cycle it increased to 80%. The average learning completeness in the prefix aspect reached 97.5% for boys and 75% for girls. If referring to the indicators of student learning outcomes, the percentage shows that the initial learning in discus throwing using modified plastic plate media is categorized as very effective for boys and girls. The average mastery of learning for aspects of how to throw reached 85% for boys and 70% for girls. Referring to the indicators of student learning outcomes, the percentage of completeness shows learning how to throw a discus throwing using a modified plastic plate, categorized as very effective for boys and girls. The average learning completeness for the final attitude aspect reached 85% for boys and 72.5% for girls. Referring to the indicators of student learning outcomes, it shows that Attitude learning in discus throwing using modified plastic plates is categorized as very effective for boys and girls.